Implementation of the 5M Health Protocol by the Community in Bakubakulu Village, Palolo District, Sigi Regency - Kantohe, Imelda; Parmi, Parmi; Arni, Fitri; Ambodale, Saiful; Purwiningsih, Sri (Journal of Midwifery and Nursing, 2024)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. Common symptoms of COVID-19 infection include symptoms of acute respiratory problems such as fever, cough and shortness of bresath. One of the obstacles in implementing health protocols is that there are still people who do not believe in the existence of the COVID-19 disease, so many people do not comply with the 5M health protocol. The aim of the research is to determine the implementation of the 5M Health Protocol by the community in Bakubakulu Village, Palolo District, Sigi Biromaru Regency. Descriptive research type. The research variable is the implementation of the 5M health protocol. The data used is primary and secondary data. Data analysis uses univariate analysis. The population in this study was 619 people and the sample was 41 people. The results of this research show that 68.3% of people implement the 5M health protocol and 31.7% do not implement the 5M health protocol. The conclusion of this research is that more and more people are implementing the 5M health protocol in Bakubakulu Village, Palolo District, Sigi Biromaru Regency. It is recommended that the Bakubakulu village government be able to discipline people who still have not implemented the 5M health protocol to prevent the spread of COVID-19, people can regularly look for information in print media.